EVALUASI TERHADAP WIDYAISWARA PADA DIKLAT TEKNIS SUBSTANTIF PENYUSUNAN BAHAN AJAR - Mohamad Fauzan (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
Widyaiswara plays an important role and determines the effectiveness of the implementation of education and training programs, so this study aims to determine the assessment of training participants on the performance of Widyaiswara in implementing learning management competencies and the constraints found during the education process in the substantive technical training in the preparation of teaching materials for Ibtidaiyah madrasah teachers. In the Ministry of Religion of the Banjar City in 2018. Researchers used a descriptive study with a qualitative approach. Data collection techniques in this study were observation sheets, researchers' notes during the learning process and unstructured interviews. Researchers used integrative qualitative data analysis techniques between interactive models and propositions through three stages of analysis, namely data reduction, display, and conclussion/verification and carried out with a basing strategy on theoretical propositions or concept propositions of academic evaluation and widyaiswara competence in the learning process of education and training. This proposition is then used as a theoretical orientation that guides the analysis of this study. The results showed that the training participants' evaluation of the widyaiswara aspects of management of educational material = 85.6, the interaction of widyaiswara with the training participants = 85.1 was GOOD, the organization of learning = 86.7, classroom management = 89.1 and the utilization of education and training facilities = 86.1 was VERY GOOD. The average acquisition of all evaluation indicators of widyaiswara's competence in learning management has fulfilled the predicate of Very Good with a score of 86.52. The assessment of widyaiswara cannot be separated from the constraints found during the learning process, namely (1) The hours of theory and practice learning are not yet proportional, (2) Products or results of training activities, (3) Limitations of the internet network, (4) Limitations of infrastructure and the location of the training, and (5) The limited time provided in the Follow-up Action activities. Key words: Evaluation, Lecturer, Education and Training